Identifikasi Topeng Bali Dengan Metode KNN (K Nearest Neighbor) - Putri, Ni Made Elvina Aryadhika; Arya Kadyanan, I Gusti Agung Gede; Supriana, I Wayan; Pramartha, Cokorda Rai Adi; Eka Karyawati, Anak Agung Istri Ngurah; Dwidasmara, Ida Bagus Gede (JELIKU (Jurnal Elektronik Ilmu Komputer Udayana); Vol 11 No 2 (2022): JELIKU Volume 11 No 2, November 2022DO - 10.24843/JLK.2022.v11.i02.p19, 2022)
Mask art is art with the form of a face covering that has various forms such as humans and animals and is an important element in dance and mask drama. Unfortunately, many tourists and also the public cannot know the name of the Balinese mask they see. To overcome this problem, a system was built to help people who want to know information about Balinese masks but do not know the names or types of Balinese masks. In developing a system that able to identify Balinese masks, KNN classification method is implemented as a method that helps identify Balinese masks. The image entered by the user is processed until a classification result is obtained which is then sent back to the system so that it can be displayed to the user. The results of the system evaluation show the percentage accuracy of the KNN algorithm is 85% with value of k = 3.